2013
DOI: 10.1007/s10695-013-9890-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of digestive enzyme activity in spotted rose snapper, Lutjanus guttatus (Steindachner, 1869) larvae

Abstract: We describe digestive enzyme activity during the larval development of spotted rose snapper, Lutjanus guttatus. Trypsin, chymotrypsin, leucine aminopeptidase, pepsin, amylase, lipase, and acid and alkaline phosphatase activities were evaluated using spectrophotometric techniques from hatching through 30 days. The spotted rose snapper larvae present the same pattern of digestive enzyme activity previously reported for other species in which pancreatic (i.e., trypsin, chymotrypsin, amylase, and lipase) and intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
8
15
1
Order By: Relevance
“…The activity of trypsin could be detected before mouth opening of stinger larvae, and similar result was observed in several species, such as Senegal sole (Martinez, Moyano, Fern andez-D ıaz & Y ufera, 1999), Asian seabass (Srichanun et al, 2013), spotted rose snapper (Galaviz et al, 2012;Moguel-Hern andez et al, 2014). The result of histological analysis revealed that the pancreas has already formed and pancreas cells began to differentiate at 3 dph along with the increasing of eosinophilic cells, indicating the ability of stinger larvae to digest the exogenous feeds.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The activity of trypsin could be detected before mouth opening of stinger larvae, and similar result was observed in several species, such as Senegal sole (Martinez, Moyano, Fern andez-D ıaz & Y ufera, 1999), Asian seabass (Srichanun et al, 2013), spotted rose snapper (Galaviz et al, 2012;Moguel-Hern andez et al, 2014). The result of histological analysis revealed that the pancreas has already formed and pancreas cells began to differentiate at 3 dph along with the increasing of eosinophilic cells, indicating the ability of stinger larvae to digest the exogenous feeds.…”
Section: Discussionsupporting
confidence: 77%
“…Then, gastric gland could be observed at 15 dph, coinciding with the remarkably increasing pepsin activity, indicating the improvement of digestive function (Peña, Dumas, Villalejo-Fuerte & Ortız-Galindo, 2003). The increasing pepsin activities have also been demonstrated with larval development in white seabass (Galaviz, Garc ıa-Gasca, Drawbridge, Alvarez-Gonz alez & L opez, 2011), Asian seabass (Srichanun et al, 2013) and spotted rose snapper (Moguel-Hern andez et al, 2014). The emergence time of gastric gland was different among fish species.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations